Spotlight on Cloud : the Future of Internet Security with Bruce Schneier - Schneier, Bruce (O'Reilly Media, Inc., 2019)
Long gone are the days when computer security was about data. Now, it's about the much more critical and personal issues of life and property. The impact of this change means two things: Data authentication and integrity concerns will trump those of confidentiality The idea of an internet without regulations will be a thing of the past While these consequences are inevitable, we can prepare for them. First, by looking at previous attempts to secure these systems. Then, by considering the appropriate technologies, laws, regulations, economic incentives, and social norms we should focus on going forward. Recorded on April 4, 2019. See the original event page for resources for further learning. Find future live events to attend or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Cloud, you'll learn about the complex, ever-evolving world of the cloud. You'll discover how successful companies have adopted and embraced this massive network of shared information and how you can follow their lead to transform your organization and prepare for the Next Economy.